2021
DOI: 10.3892/mmr.2021.11896
|View full text |Cite
|
Sign up to set email alerts
|

Promotive role of microRNA‑150 in hippocampal neurons apoptosis in vascular dementia model rats

Abstract: Cognitive impairment is one of the primary features of vascular dementia (VD). However, the specific mechanism underlying the regulation of cognition function in VD is not completely understood. The present study aimed to explore the effects of microRNA (miR)-150 on VD. To determine the effects of miR-150 on cognitive function and hippocampal neurons in VD model rats, rats were subjected to intracerebroventricular injections of miR-150 antagomiR. The Morris water maze test results demonstrated that spatial lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Therefore, the neuronal impairment will likely cause changes in structural synaptic plasticity. Previous studies demonstrated via Nissl staining that VD rats displayed significantly neuron structural changes in the hippocampal 45 . The immunostaining results in our study demonstrated that treadmill exercise pretreatment can ameliorate VD-induced the decrease of neuron density in the medial prefrontal cortex region of VD rats, as determined by NeuN immunostaining.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, the neuronal impairment will likely cause changes in structural synaptic plasticity. Previous studies demonstrated via Nissl staining that VD rats displayed significantly neuron structural changes in the hippocampal 45 . The immunostaining results in our study demonstrated that treadmill exercise pretreatment can ameliorate VD-induced the decrease of neuron density in the medial prefrontal cortex region of VD rats, as determined by NeuN immunostaining.…”
Section: Discussionmentioning
confidence: 89%
“…miR-153 is elevated in the plasma of dementia patients and rats subjected to 2VO surgery and may serve as a drug target for VD (Yan et al, 2020). Wei and others (Wei et al, 2021) have shown that knockdown of miR-150 improves VD symptoms via regulating the expression of homeobox A1 (HOXA1) in vivo and in vitro. In addition, abnormal miR-143-3p expression is related to ischemic brain injury (Zhou et al, 2021) and acute ischemic stroke (Tiedt et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…miR‐150‐5p was also shown to increase blood brain barrier permeability in response to CAO by targeting Tie2 (Fang et al, 2016). In a mouse model of vascular dementia, miR‐150 was upregulated in hippocampal neurons and responsible for neuronal apoptosis by negatively regulating HOXA1 expression (Wei et al, 2021). Although studies of miR‐150‐5p within the CNS indicate its role to be a negative regulator of angiogenesis, some studies of miR‐150‐5p in the periphery indicate the opposite function and increase migration and proliferation (Luo et al, 2018; Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%